Impact of allele-level HLA matching on outcomes after myeloablative single unit umbilical cord blood transplantation for hematologic malignancy - Eapen, Mary (American Society of Hematology, 2014)
We studied the effect of allele-level matching at human leukocyte antigen (HLA)-A, -B, -C, and -DRB1 in 1568 single umbilical cord blood (UCB) transplantations for hematologic malignancy. The primary end point was nonrelapse mortality (NRM). Only 7% of units were allele matched at HLA-A, -B, -C, and -DRB1; 15% were mismatched at 1, 26% at 2, 30% at 3, 16% at 4, and 5% at 5 alleles. In a subset, allele-level HLA match was assigned using imputation; concordance between HLA-match assignment and outcome correlation was confirmed between the actual and imputed HLA-match groups. Compared with HLA-matched units, neutrophil recovery was lower with mismatches at 3, 4, or 5, but not 1 or 2 alleles. NRM was higher with units mismatched at 1, 2, 3, 4, or 5 alleles compared with HLA-matched units. The observed effects are independent of cell dose and patient age. These data support allele-level HLA matching in the selection of single UCB units.